Thermoplastic resin composition, molded article, and member for communication device

By adding LDS additives and polyphenylene ether-based resins with specific particle distances to the thermoplastic resin composition, the problem of insufficient dielectric properties during molding at high temperature is solved, and excellent antenna performance is achieved.

CN119732183APending Publication Date: 2025-03-28ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202480003406.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-23
Filing Date
2024-02-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

When the conventional thermoplastic resin composition for LDS is molded at high temperature, the dielectric characteristics of the obtained molded body are insufficient, resulting in poor antenna performance.

Method used

By adding a specific LDS additive to the thermoplastic resin composition, the particle distance between the particles is between 2.2 and 3.2 μm, and combining a polyphenylene ether-based resin and a block copolymer, a resin composition with a Vickers softening temperature of 90°C or above was prepared.

Benefits of technology

Regardless of the forming conditions, especially at high temperatures, excellent antenna performance can be achieved and good fluidity and electrical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005241086630000051
    Figure BDA0005241086630000051
  • Figure BDA0005241086630000121
    Figure BDA0005241086630000121
  • Figure BDA0005241086630000131
    Figure BDA0005241086630000131
Patent Text Reader

Abstract

The purpose of the present invention is to provide a thermoplastic resin composition which constitutes a material for a member for a communication device, and which has excellent antenna performance regardless of injection molding conditions, particularly even when injection molding is performed at high temperatures. This thermoplastic resin composition contains a polyphenylene ether-based resin and a laser direct structuring additive (LDS additive), the distance between particles of the LDS additive being 2.2-3.2 [mu] m, the Vickers softening temperature being 90 DEG C or higher, and the water absorption being 1.5% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a communication device component, and more particularly to a molded body composed of a thermoplastic resin composition containing a laser direct structuring additive, and a communication device component having a conductive portion on the surface of the molded body. Background Art

[0002] In recent years, as mobile communication devices such as mobile phones have become lighter and smaller, the demand for lighter and smaller components used in communication devices such as dielectric antennas has also increased. Therefore, methods for manufacturing antennas that can be designed three-dimensionally in smartphones, wireless headphones, personal computers, etc. are being sought.

[0003] As one of the technologies for forming such a three-dimensional antenna, laser direct structuring (hereinafter sometimes referred to as "LDS") has attracted attention. Figure 1 (a)~ Figure 1 (d) is a technique in which a surface of a molded article composed of a thermoplastic resin composition for LDS containing an LDS additive is irradiated with laser light ( Figure 1 (a)) Activate only the part irradiated with laser ( Figure 1 (b)), applying a metal ( Figure 1 (c)), thereby forming a conductive portion (plating layer, etc.) Figure 1 (d)). This technology is characterized in that a metal structure such as an antenna can be directly manufactured on the surface of a resin substrate without using an adhesive or the like, thereby enabling miniaturization of components.

[0004] Here, Figure 2 This is a schematic diagram to illustrate the process of installing a circuit using LDS technology. After designing the circuit ( Figure 2 (a)), prepare a resin molded body ( Figure 2 (b)) irradiates the laser along the designed circuit shape ( Figure 2 (c)), and then plating is performed to obtain a metal structure of a desired shape ( Figure 2 (d)).

[0005] For example, such LDS technology is disclosed in Patent Documents 1 to 3. LDS is one of the 3D-MID technologies, and as examples of components used, Public Document 1 discloses examples of antennas for smartphones, antennas for wearable devices, and antennas for automotive use. In addition, Public Document 2 discloses photographs of examples of antennas.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Publication No. 2000-503817

[0009] Patent Document 2: Japanese Patent Application No. 2004-534408

[0010] Patent Document 3: International Publication No. WO2009 / 141800

[0011] Non-patent literature 1: Hiroyuki Ueda プロセスによるMID manufacturing surface technology (based on MID Manufacturing by Process, Surface Technology), 2020, Vol. 71, No. 4, P.268-272

[0012] Non-patent document 2: Toshiki Niino, MID: Journal of Electronic Packaging Society Aiming at Metal-Resin Composites (MID: Journal of the Society of Electronic Packaging), 2017, Vol. 20, No. 6, P. 268-272 Summary of the invention

[0013] Problems to be solved by the invention

[0014] The above-mentioned communication equipment components composed of the thermoplastic resin composition for LDS require electrical properties and good fluidity. In recent years, it is required to exhibit antenna characteristics in high-frequency bands above 1 GHz, so low dielectric properties are required. In addition, as mentioned above, there is a tendency for communication equipment itself to be lightweight and miniaturized. In order to respond to such needs, various components for communication equipment are also increasingly miniaturized. For such small components, it is necessary to have a thin-walled shape.

[0015] Generally, when molding a small molded product with a thin wall portion, the molding temperature is set high. However, for conventional thermoplastic resin compositions for LDS, if molding is performed at a high temperature, the dielectric properties of the obtained molded product may be insufficient. As a result, the performance as an antenna may also be insufficient.

[0016] Therefore, an object of the present invention is to provide a thermoplastic resin composition, a molded article, and a communication device component that can achieve excellent antenna performance regardless of molding conditions, particularly even when molding is performed at high temperatures.

[0017] Means for solving problems

[0018] The present inventors have conducted intensive studies to solve the above problems and have found that excellent antenna performance can be exhibited regardless of molding conditions by making the LDS additive contained in the thermoplastic resin composition constituting the communication device component into a specific dispersed state, thereby completing the present invention.

[0019] That is, the present invention is as follows.

[0020] [1] A thermoplastic resin composition, characterized in that:

[0021] The thermoplastic resin composition comprises a polyphenylene ether resin and a laser direct structuring additive (LDS additive).

[0022] The distance between particles of the above LDS additive is 2.2 to 3.2 μm.

[0023] The thermoplastic resin composition has a Vickers softening temperature of 90° C. or higher and a water absorption rate of 1.5% or less.

[0024] [2] A molded article composed of a thermoplastic resin composition and having a conductive portion formed on the surface thereof, wherein:

[0025] The thermoplastic resin composition comprises a polyphenylene ether resin and a laser direct structuring additive (LDS additive).

[0026] The distance between particles of the LDS additive in the thermoplastic resin composition is 2.2 to 3.2 μm.

[0027] The thermoplastic resin composition has a Vickers softening temperature of 90° C. or higher and a water absorption rate of 1.5% or less.

[0028] [3] The molded article described in [2], wherein the conductive portion is formed by laser direct molding.

[0029] [4] A communication device component, comprising the molded article described in [2] or [3].

[0030] [5] The communication device component described in [4], characterized in that the LDS additive is a compound containing antimony and tin.

[0031] [6] The component for communication equipment as described in [4], characterized in that when the thermoplastic resin composition is observed under a microscope, 220 or less of the LDS additive are observed in one field of view (62.02 μm×39.77 μm).

[0032] [7] The component for communication equipment as described in [4], characterized in that the maximum particle size of the above-mentioned LDS additive is greater than 2.2 μm.

[0033] [8] The communication device component described in [4], characterized in that the content of the copper chromate compound as the LDS additive is less than 5 parts by mass based on 100 parts by mass of the thermoplastic resin composition.

[0034] [9] The communication device component described in [4], wherein the content of the LDS additive is 3 parts by mass or more and less than 20 parts by mass based on 100 parts by mass of the thermoplastic resin composition.

[0035]

[10] The component for communication equipment as described in [4], characterized in that the above-mentioned thermoplastic resin composition contains the following block copolymer and / or a hydrogenated product of the block copolymer, wherein the block copolymer contains at least one block mainly composed of aromatic vinyl monomer units and at least one block mainly composed of conjugated diene monomer units.

[0036]

[11] The communication device component according to [4], wherein the thermoplastic resin composition has a deflection temperature under load (DTUL) of 90°C or higher.

[0037]

[12] The component for communication equipment as described in [4], characterized in that the dielectric constant of the thermoplastic resin composition is 3.0 or less and the dielectric loss tangent is 0.008 or less.

[0038]

[13] The component for communication equipment as described in [4], characterized in that the dielectric loss tangent of the thermoplastic resin composition after being immersed in hot water at 80°C for 144 hours is 0.03 or less.

[0039]

[14] The component for communication equipment as described in [4], characterized in that it is a component for an antenna.

[0040] Effects of the Invention

[0041] According to the present invention, it is possible to provide a thermoplastic resin composition, a molded article, and a communication device component that can achieve excellent antenna performance regardless of molding conditions even when molding is performed at high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 (a) to (d) are diagrams for explaining the process of plating by laser direct structuring technology.

[0043] Figure 2 (a) to (d) are diagrams for explaining the process of plating a resin molded body and forming a circuit by laser direct structuring technology.

[0044] Figure 3 (a) and (b) are diagrams for explaining antennas used for evaluating antenna performance during high temperature molding in the example. DETAILED DESCRIPTION

[0045] The content of the present invention is described in detail below.

[0046] The communication device component of the present embodiment includes: a molded body made of a thermoplastic resin composition; and a conductive portion formed on the surface of the molded body.

[0047] [Thermoplastic resin composition, molded article]

[0048] The thermoplastic resin composition constituting the molded article of the present embodiment contains (A) a matrix resin and (B) an LDS additive.

[0049] The above-mentioned (A) base resin comprises (Aa) a polyphenylene ether resin, and preferably optionally comprises (Ab) a block copolymer comprising at least one block mainly composed of aromatic vinyl monomer units and at least one block mainly composed of conjugated diene monomer units and / or a hydrogenated product of the block copolymer.

[0050] ((A) Base resin)

[0051] The above-mentioned (A) matrix resin refers to the resin component other than the inorganic filler, etc. It should be noted that the (B) LDS additive described later is not included. As the resin component, at least a polyphenylene ether resin is included, and in addition, various resins used for molding purposes may be included, such as polyester resins, polyamide resins, polycarbonate resins, vinyl resins, olefin resins, acrylic resins, polyphenylene sulfide, aromatic resins, etc.

[0052] (Aa) Polyphenylene ether resin

[0053] Specific examples of the polyphenylene ether resin (Aa) (hereinafter sometimes referred to as "component (Aa)") include poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), etc. In addition, polyphenylene ether copolymers such as copolymers of 2,6-dimethylphenol and other phenols (for example, copolymers with 2,3,6-trimethylphenol and copolymers with 2-methyl-6-butylphenol described in Japanese Patent Publication No. 52-17880) can also be used.

[0054] Among these, particularly preferred polyphenylene ethers include poly(2,6-dimethyl-1,4-phenylene ether), a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, or a mixture thereof.

[0055] Examples of the component (Aa) include a homopolymer having a repeating unit structure represented by the following formula (1) and a copolymer having a repeating unit structure represented by the following formula (1).

[0056] [Chemistry 1]

[0057]

[0058] In the above formula (1), R 1 , R 2 , R 3 and R 4 Each is independently a monovalent group selected from the group consisting of a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a halogenated alkyl group, an aminoalkyl group, a hydrocarbyloxy group, and a halogenated hydrocarbyloxy group in which a halogen atom and an oxygen atom are separated by at least two carbon atoms.

[0059] In addition, the above-mentioned (Aa) component may be used individually by 1 type, or may use 2 or more types together.

[0060] The method for producing the polyphenylene ether resin (Aa) is not particularly limited as long as it can be obtained by a known method. For example, there can be mentioned a method in which, for example, 2,6-xylenol is produced by oxidative polymerization using a complex of a cuprous salt and an amine as a catalyst, a method described in U.S. Pat. No. 3,306,874, U.S. Pat. No. 3,306,875, U.S. Pat. No. 3,257,357, and U.S. Pat. No. 3,257,358, Japanese Patent Application Publication Nos. 50-51197, 52-17880, and 63-152628.

[0061] The reduced viscosity of the polyphenylene ether resin (Aa) (0.5 g / dL chloroform solution, 30° C., measured using an Ubbelohde viscometer) is preferably in the range of 0.30 to 0.80 dL / g, more preferably 0.35 to 0.75 dL / g, and most preferably 0.38 to 0.55 dL / g. When the reduced viscosity of the polyphenylene ether resin (Aa) is within the above range, the properties such as impact resistance and heat resistance are excellent.

[0062] Among the polyphenylene ether-based resins (Aa), a blend of two or more polyphenylene ethers having different reduced viscosities can also be preferably used.

[0063] In order to stabilize the polyphenylene ether resin (Aa), various known stabilizers may be used as appropriate. Examples of the stabilizer include metal stabilizers such as zinc oxide and zinc sulfide, hindered phenol stabilizers, phosphorus stabilizers, hindered amine stabilizers and other organic stabilizers.

[0064] The amount of these stabilizers to be blended is preferably less than 5 parts by mass based on 100 parts by mass of the polyphenylene ether-based resin (Aa).

[0065] Furthermore, known additives and the like that can be added to the (Aa) polyphenylene ether-based resin may be added in an amount of less than 10 parts by mass based on 100 parts by mass of the (Aa) polyphenylene ether-based resin.

[0066] The component (Aa) may be a modified polyphenylene ether obtained by reacting the homopolymer and / or the copolymer with a styrene-based monomer or a derivative thereof, and / or an α,β-unsaturated carboxylic acid or a derivative thereof.

[0067] Here, the graft amount or addition amount of the styrene-based monomer or its derivative and / or the α,β-unsaturated carboxylic acid or its derivative is preferably 0.01 to 10% by mass relative to 100% by mass of the component (Aa).

[0068] Examples of the method for producing the modified polyphenylene ether include a method of reacting the modified polyphenylene ether in a molten state, a solution state, or a slurry state at a temperature of 80 to 350° C. in the presence or absence of a radical initiator.

[0069] As the polyphenylene ether, a mixture of the homopolymer and / or copolymer and the modified polyphenylene ether in any ratio may be used.

[0070] From the perspective of achieving both heat resistance and low dielectric constant and low dielectric loss tangent, the content of the polyphenylene ether resin (Aa) is preferably 30 parts by mass or more, preferably 40 parts by mass or more, and more preferably 50 parts by mass or more, relative to 100 parts by mass of the matrix resin (A). In addition, from the perspective of moldability, it is preferably 95 parts by mass or less.

[0071] (Ab) a block copolymer comprising at least one block mainly composed of aromatic vinyl monomer units and at least one block mainly composed of conjugated diene monomer units and / or a hydrogenated product of the block copolymer

[0072] In this embodiment, (Ab) a block copolymer comprising at least one block with aromatic vinyl monomer units as the main body and at least one block with conjugated diene monomer units as the main body and / or a hydrogenated product of the block copolymer (hereinafter sometimes referred to as "(Ab) component") may be further included, preferably including this component. The above-mentioned (Ab) block copolymer comprising at least one block with aromatic vinyl monomer units as the main body and at least one block with conjugated diene monomer units as the main body and / or a hydrogenated product of the block copolymer refers to a non-hydrogenated block copolymer comprising at least one aromatic vinyl polymer block with aromatic vinyl monomer units as the main body and at least one conjugated diene polymer block with conjugated diene monomer units as the main body and / or a hydrogenated product of the block copolymer.

[0073] It should be noted that, with respect to the above-mentioned aromatic vinyl polymer block, "mainly composed of aromatic vinyl monomer units" means that 50% by mass or more of the block is an aromatic vinyl monomer unit. More preferably, the aromatic vinyl monomer unit is 70% by mass or more, further preferably 80% by mass or more, and most preferably 90% by mass or more.

[0074] In addition, the term "mainly composed of conjugated diene monomer units" in the conjugated diene polymer block also refers to a block in which 50% by mass or more of the conjugated diene monomer units are present. More preferably, the conjugated diene monomer units are present in an amount of 70% by mass or more, further preferably 80% by mass or more, and most preferably 90% by mass or more.

[0075] In addition, the aromatic vinyl polymer block may be, for example, a copolymer block in which a small amount of a conjugated diene compound is randomly bonded to the aromatic vinyl polymer block. In addition, the conjugated diene polymer block may also be, for example, a copolymer block in which a small amount of an aromatic vinyl compound is randomly bonded to the conjugated diene polymer block.

[0076] The aromatic vinyl compound for forming the aromatic vinyl monomer unit is not particularly limited, and examples thereof include styrene, α-methylstyrene, vinyltoluene, and the like. One or more compounds selected from these can be used, and among them, styrene is particularly preferred.

[0077] The conjugated diene compound for forming the conjugated diene polymer block is not particularly limited, and examples thereof include butadiene, isoprene, piperylene, and 1,3-pentadiene. One or more compounds selected from these can be used, and among them, butadiene, isoprene, and a combination thereof are preferred.

[0078] In the microstructure of the conjugated diene polymer block portion of the block copolymer, the 1,2-vinyl content or the total amount of the 1,2-vinyl content and the 3,4-vinyl content (total vinyl bond content) is preferably 5 to 80%, more preferably 10 to 70%.

[0079] In addition, the total vinyl bond amount can be measured using an infrared spectrophotometer.

[0080] The non-hydrogenated block copolymer used in the production of the hydrogenated product of the block copolymer (hydrogenated block copolymer) is preferably a block copolymer in which the aromatic vinyl polymer block (A) and the conjugated diene polymer block (B) have a bonding form selected from the group consisting of AB type, ABA type, and ABAB type. Among these, block copolymers having different bonding forms may be used in combination.

[0081] Among these, it is more preferred to have a bonding form selected from the ABA type and the ABAB type, and it is even more preferred to have an ABA type bonding form.

[0082] Furthermore, the component (Ab) used in the present embodiment is preferably a partially hydrogenated block copolymer (partially hydrogenated block copolymer).

[0083] The partially hydrogenated block copolymer is a copolymer in which the aliphatic double bonds of the conjugated diene polymer block are controlled within a range of greater than 0% and less than 100% by hydrogenating the non-hydrogenated block copolymer. The partially hydrogenated block copolymer preferably has a hydrogenation rate of 50% or more and less than 100%, more preferably 80% or more and less than 100%, and most preferably 98% or more and less than 100%.

[0084] The number average molecular weight of the component (Ab) is preferably 30,000 or more and less than 300,000. When the number average molecular weight is within this range, a composition having excellent fluidity, impact strength, and flame retardancy can be obtained.

[0085] The evaluation method of the number average molecular weight of the component (Ab) in the resin composition is as follows.

[0086] That is, the component (Ab) is separated using a solvent (e.g., chloroform) that has good solubility in the component (Ab) and poor solubility in the polyphenylene ether resin (Aa). The component (Ab) is measured using a gel permeation chromatography apparatus [GPC SYSTEM 21: manufactured by Showa Denko K.K.] using an ultraviolet spectrophotometer [UV-41: manufactured by Showa Denko K.K.], and the number average molecular weight is calculated by conversion using standard polystyrene.

[0087] It should be noted that the measurement conditions can be as follows [Solvent: chloroform, temperature: 40°C, column: sample side (KG, K-800RL, K-800R), reference side (K-805L×2), flow rate 10 mL / min, measurement wavelength: 254 nm, pressure 15 to 17 kg / cm 2 )].

[0088] In addition, when measuring the number average molecular weight, low molecular weight components may be detected due to catalyst deactivation during polymerization. In this case, the low molecular weight components are not included in the molecular weight calculation. The low molecular weight components refer to components with a molecular weight of 3000 or less. Usually, the calculated correct molecular weight distribution (weight average molecular weight / number average molecular weight) is within the range of 1.0 to 1.1.

[0089] Among these block copolymers as the component (Ab) that can be used in the present embodiment, as long as it does not violate the purpose of the present embodiment, various substances such as substances with different bonding forms, substances with different types of aromatic vinyl compounds, substances with different types of conjugated diene compounds, substances with different 1,2-bonded vinyl contents or substances with different 1,2-bonded vinyl contents and 3,4-bonded vinyl contents, substances with different aromatic vinyl compound component contents, substances with different hydrogenation rates, etc. can be mixed and used.

[0090] Furthermore, the block copolymers as the component (Ab) that can be used in the present embodiment may be block copolymers in which all or part of the block copolymers are modified.

[0091] The modified block copolymer referred to herein refers to a block copolymer modified with at least one modifying compound having at least one carbon-carbon double bond or triple bond and at least one carboxylic acid group, acid anhydride group, amino group, hydroxyl group or glycidyl group in its molecular structure.

[0092] Examples of methods for preparing the modified block copolymer include: (1) a method of melt-kneading and reacting the block copolymer with a modifying compound in a temperature range of above the softening point of the block copolymer and below 250°C in the presence or absence of a free radical initiator; (2) a method of reacting the block copolymer and the modifying compound in a solution at a temperature below the softening point of the block copolymer; (3) a method of reacting the block copolymer and the modifying compound in a non-molten state at a temperature below the softening point of the block copolymer, etc. Any of these methods may be used, but method (1) is preferred. Among (1), the method performed in the presence of a free radical initiator is most preferred.

[0093] As the "at least one modifying compound having at least one carbon-carbon double bond or triple bond and at least one carboxylic acid group, acid anhydride group, amino group, hydroxyl group or glycidyl group in its molecular structure" mentioned here, the same modifying compounds as those described in the modified polyphenylene ether can be used.

[0094] The content of the component (Ab) is preferably 1 to 40 parts by mass, more preferably 2 to 35 parts by mass, and even more preferably 2 to 30 parts by mass, based on 100 parts by mass of the polyphenylene ether resin (Aa).

[0095] In addition, the total content of the polyphenylene ether resin (Aa) and the component (Ab) is preferably 30 parts by mass or more, more preferably 35 parts by mass or more, relative to 100 parts by mass of the matrix resin (A). By making the total content of the components (Aa) and (Ab) within the above range, heat resistance, low dielectric constant, and low dielectric loss tangent can be achieved, and the (B) LDS additive described later can be made into an arbitrary dispersion form.

[0096] ·(Ac) Polystyrene resin

[0097] The above-mentioned (A) matrix resin may include a polystyrene resin. Examples of the polystyrene resin include atactic polystyrene, rubber-reinforced polystyrene (high impact polystyrene, HIPS), styrene-acrylonitrile copolymer (SAN) having a styrene content of 50% by weight or more, and ABS resin obtained by reinforcing the styrene-acrylonitrile copolymer with rubber, among which atactic polystyrene and / or high impact polystyrene are preferably included.

[0098] In addition, the above-mentioned polystyrene-based resins may be used alone or in combination of two or more.

[0099] In the present embodiment, the content of the (Ac) polystyrene resin is preferably 0 to 100 parts by mass, more preferably 0 to 90 parts by mass, and even more preferably 0 to 80 parts by mass, based on 100 parts by mass of the (Aa) polyphenylene ether resin.

[0100] Other resin components

[0101] Examples of other resin components in the matrix resin (A) of the present embodiment include polyolefins such as polyester and polypropylene, polyamide, polyphenylene sulfide, and olefin-based thermoplastic elastomers.

[0102] Examples of the olefin-based thermoplastic elastomer include polyolefin homopolymers such as polyethylene and polypropylene, and polyolefin copolymers such as ethylene-propylene copolymers, ethylene-butene copolymers, and ethylene-octene copolymers. In particular, examples of polyethylene homopolymers include high-pressure low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and high-density polyethylene (HDPE).

[0103] The specific preferred addition amount of each of the other resin components is 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less, when the entire thermoplastic resin composition is taken as 100% by mass.

[0104] The preferred amount of other resin components added is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on 100% by mass of the entire thermoplastic resin composition.

[0105] In particular, from the perspective of achieving low dielectric loss tangent and low dielectric constant, the total content of polyamide and polyphenylene sulfide is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, further preferably 1 part by mass or less, and may be 0 parts by mass, relative to 100 parts by mass of the (A) matrix resin.

[0106] ((B)LDS additive)

[0107] The thermoplastic resin composition constituting the molded article of the communication device component of the present embodiment further contains (B) a laser direct structuring additive (LDS additive) in addition to the above-mentioned (A) matrix resin.

[0108] By including the above-mentioned LDS additive, a plating layer can be formed on the surface of the obtained resin molded product by LDS technology, and a conductive portion can be formed on the surface. In this case, the lower the dielectric constant and dielectric loss tangent of the thermoplastic resin composition having the conductive portion, the better the characteristics as an antenna.

[0109] In addition, practically, the plating deposition property for forming the conductive portion and the adhesion of the deposited plating layer are required. In order to meet these requirements, it is necessary to select appropriate thermoplastic resins and LDS additives.

[0110] It should be noted that the above-mentioned LDS technology is the following technology: a pulsed laser of near-infrared light with a wavelength of 1064nm is irradiated onto a resin molded product under the conditions of an output power of 7W, a frequency of 50kHz, and a speed of 2000mm / s, and as a subsequent plating process, it is immersed in an electroless plating bath to selectively form a plating layer only on the laser irradiated part.

[0111] The (B) LDS additive is a compound which, by adding a specific amount (about 3 to 15 parts by mass relative to 100 parts by mass of the entire thermoplastic resin composition), can form a conductive portion on the surface of a molded article by the above-mentioned LDS technique.

[0112] Among the above-mentioned (B) LDS additives, from the perspective of improving plating properties, it is preferred that the additive contains at least one of copper, antimony, tin, aluminum and zinc, more preferably contains a copper chromate compound and / or an oxide containing antimony and tin, and further preferably contains an oxide containing at least antimony and tin.

[0113] More specifically, the (B) LDS additive is an embodiment of an oxide containing at least one of antimony and phosphorus and tin, preferably an oxide containing antimony and tin. This is because the compound containing antimony and tin is easier to control dispersion than the copper chromate compound, so stable dielectric constant and dielectric loss tangent values ​​can be obtained.

[0114] The oxide containing antimony and tin is more preferably an oxide in which the tin content is larger than the antimony content, and further preferably an oxide in which the amount of tin is 80 mass % or more based on the total amount of tin and antimony.

[0115] More specifically, the above-mentioned (B) LDS additive includes tin oxide doped with antimony, tin oxide doped with antimony oxide, tin oxide doped with phosphorus, and tin oxide doped with phosphorus oxide. Preferably, it is tin oxide doped with antimony and tin oxide doped with antimony oxide, and more preferably, it is tin oxide doped with antimony oxide.

[0116] The (B) LDS additive may be a synthetic product or a commercial product. In addition, the commercial products may be products sold for other purposes other than those sold as LDS additives as long as they meet the requirements of the LDS additive in this embodiment.

[0117] It should be noted that the above-mentioned (B) LDS additive may be used alone or in combination of two or more.

[0118] The above-mentioned (B) LDS additive may contain trace amounts of other metals in addition to antimony and tin. Examples of other metals include copper, chromium, lead, indium, iron, cobalt, nickel, zinc, cadmium, silver, bismuth, arsenic, manganese, magnesium, and calcium. These metals may exist in the form of oxides.

[0119] The content of metal oxides other than antimony and tin is preferably 30% by mass or less, and particularly, copper chromate is preferably less than 5 parts by mass (excluding 5 parts by mass or more) per 100 parts by mass of the thermoplastic resin composition.

[0120] In addition, the content of the (B) LDS additive in the thermoplastic resin composition is preferably 1.0 parts by mass or more, more preferably 2.0 parts by mass or more, further preferably 3.0 parts by mass or more, more preferably 5.0 parts by mass or more, and more preferably 6.0 parts by mass or more, relative to 100 parts by mass of the thermoplastic resin as a whole. By making the content of the (B) LDS additive 1.0 parts by mass or more, there is a tendency for the plating property to be further improved. In addition, the content of the (B) LDS additive in the thermoplastic resin composition is preferably 30.0 parts by mass or less, more preferably 25.0 parts by mass or less, further preferably 20.0 parts by mass or less, further preferably 15.0 parts by mass or less, and further preferably 12.0 parts by mass or less, relative to 100 parts by mass of the thermoplastic resin. By making the content of the (B) LDS additive 30.0 parts by mass or less, the resin composition has a tendency to further show a low dielectric constant and a low dielectric loss tangent.

[0121] In addition, in the thermoplastic resin composition, the (B) LDS additive may contain only one kind or two or more kinds. When two or more kinds are contained, the total amount is preferably within the above range.

[0122] ((f) Flame retardant)

[0123] The thermoplastic resin composition may further include (f) a flame retardant.

[0124] (f) Flame retardants include inorganic flame retardants such as magnesium hydroxide and aluminum hydroxide; nitrogen-containing cyclic compounds such as melamine, cyanuric acid, and salts thereof; organic phosphates such as triphenyl phosphate, triphenyl phosphate hydroxide, bisphenol A bis(diphenyl phosphate), and derivatives thereof; phosphoric acid nitrogen-containing compounds such as ammonium polyphosphate and melamine polyphosphate; phosphazene compounds described in Japanese Unexamined Patent Publication No. 11-181429; boric acid compounds such as zinc borate; silicone oils; red phosphorus; phosphinates described in International Publication No. 2007 / 055147; mixtures thereof; and the like. Among these, nitrogen-containing cyclic compounds, organic phosphates, phosphoric acid nitrogen-containing compounds, phosphazene compounds, boric acid compounds, silicone oils, and phosphinates are preferred, and bisphenol A bis(diphenyl phosphate) and its derivatives, phosphinates, and mixtures thereof are more preferred.

[0125] The phosphoric acid ester as the flame retardant (f) mentioned above includes those represented by the following formula (I) or (II).

[0126] [Chemistry 2]

[0127]

[0128] In the above formula, Q1, Q2, Q3, and Q4 represent an alkyl group having 1 to 6 carbon atoms or hydrogen, R1, R2, R3, and R4 represent a methyl group or hydrogen, n represents an integer greater than 1, n1 and n2 represent an integer from 0 to 2, and m1, m2, m3, and m4 represent an integer from 1 to 3.

[0129] Note that the condensed phosphate ester represented by the formula (II) has a smaller dipole moment than the condensed phosphate ester represented by the formula (I), and thus has excellent dielectric properties.

[0130] Among them, from the perspective of dipole moment, the preferred condensed phosphate ester is a substance containing more than 50% of the following phosphate ester, wherein Q1, Q2, Q3, and Q4 in formula (II) are hydrogen or methyl; R1 is hydrogen; and n is in the range of 1 to 3, especially n is 1.

[0131] The flame retardant is generally a commercially available product, and examples thereof include CR-741, CR-747, CR733S, and PX-200 from Daihachi Chemical Co., Ltd.

[0132] The phosphinates include at least one selected from the group consisting of a phosphinate represented by the following formula (1), a diphosphinate represented by the following formula (2), and condensates thereof.

[0133] [Chemistry 3]

[0134]

[0135] In the above formula (1), R11 and R12 are each independently a linear or branched alkyl group having 1 to 6 carbon atoms, an aryl group, or a phenyl group; M1 is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion and a protonated nitrogenous base; a is an integer of 1 to 3; m is an integer of 1 to 3; and a=m.

[0136] [Chemistry 4]

[0137]

[0138] In the above formula (2), R21 and R22 are each independently a linear or branched alkyl group, an aryl group, or a phenyl group having 1 to 6 carbon atoms; R23 is a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 6 to 10 carbon atoms, or an arylalkylene group having 6 to 10 carbon atoms; M2 is at least one selected from the group consisting of calcium ion, magnesium ion, aluminum ion, zinc ion, bismuth ion, manganese ion, sodium ion, potassium ion and a protonated nitrogenous base; b is an integer of 1 to 3; j is 1 or 2; n is an integer of 1 to 3; b·j=2n.

[0139] In addition, as the flame retardant (f) mentioned above, an inorganic or organic flame retardant containing substantially no halogen is preferred.

[0140] In this specification, substantially free of halogen means that the halogen concentration in the resin composition containing the (f) flame retardant is less than 2 mass %. The halogen concentration in the resin composition containing the (f) flame retardant is preferably less than 1 mass %, more preferably less than 0.5 mass %.

[0141] The content of the flame retardant (f) may be in the range of 1 to 40 parts by weight relative to 100 parts by weight of the matrix resin (A). When the content of the flame retardant (f) is 1 part by weight or more, a flame retardant effect can be obtained, and when the content is 40 parts by weight or less, a decrease in mechanical strength and heat resistance can be reduced.

[0142] As a method for adding the flame retardant (f), for example, there can be mentioned a method of mixing the flame retardant (f) into the dispersed phase resin and the continuous phase resin in the resin composition, respectively. Specifically, there can be mentioned a method of mixing one or more flame retardants selected from the group consisting of phosphate esters, nitrogen-containing cyclic compounds, phosphoric acid-based nitrogen-containing compounds, phosphazene-based compounds, boric acid compounds, silicone oils, and phosphinates into the resin forming the dispersed phase and the resin forming the continuous phase.

[0143] Among them, it is preferred to mix different flame retardants in the dispersed phase and the continuous phase, respectively. Specifically, it is preferred to mix at least one selected from the group consisting of phosphate esters, phosphoric acid nitrogen-containing compounds, phosphazene compounds and silicone oils in the dispersed phase, and mix at least one selected from the group consisting of nitrogen-containing cyclic compounds, phosphoric acid nitrogen-containing compounds, boric acid compounds and phosphinates in the continuous phase.

[0144] (Anti-drip agent)

[0145] In addition, the above-mentioned thermoplastic resin composition may further contain an anti-dripping agent.

[0146] Examples of the anti-dripping agent include fluorine-based polymers such as tetrafluoroethylene.

[0147] It should be noted that the content of the anti-dripping agent is preferably such that the halogen concentration is less than 2% by mass when the entire thermoplastic resin composition is 100% by mass. In this case, the anti-dripping agent also functions as a flame retardant.

[0148] (Colorant)

[0149] In addition, the thermoplastic resin composition may further contain a colorant.

[0150] The method for coloring the thermoplastic resin composition is not particularly limited, and one or more colorants selected from known organic dyes / pigments and inorganic pigments can be used.

[0151] Examples of organic dyes / pigments include azo pigments such as azo lake pigments, benzimidazolone pigments, diarylide pigments, and condensed azo pigments, phthalocyanine pigments such as phthalocyanine blue and phthalocyanine green, isoindolinone pigments, quinophthalone pigments, quinacridone pigments, perylene pigments, anthraquinone pigments, perinone pigments, condensed polycyclic pigments such as dioxazine violet, azine pigments, and carbon black.

[0152] Among them, as carbon black, it is preferred that the dibutyl phthalate (DBP) absorption is less than 250 mL / 100 g, preferably less than 150 mL / 100 g, and the nitrogen adsorption specific surface area is less than 900 m 2 / g, more preferably less than 400m 2 When these are within this range, a composition having particularly excellent colorability, mechanical strength, and flame retardancy can be obtained.

[0153] The DBP absorption value and the nitrogen adsorption specific surface area referred to herein are values ​​measured by the methods specified in ASTM D2414 and JIS K6217, respectively.

[0154] Examples of azine dyes include Solvent Black 5 (CI50415, CAS No. 11099-03-9), Solvent Black 7 (CI50415:1, CAS No. 8005-20-5 / 101357-15-7), and Acid Black 2 (CI50420, CAS No. 8005-03-6 / 68510-98-5) in the Color Index.

[0155] Examples of the inorganic pigment include metal oxides other than iron oxide such as zinc oxide and chromium oxide, and composite metal oxides such as titanium yellow, cobalt blue, and ultramarine blue.

[0156] Regarding the preferred amount of the colorant added, when the resin composition as a whole is 100% by mass, the carbon black is 2% by mass or less, the azine dye is 2% by mass or less, and the inorganic pigment is 8% by mass or less. Regarding the more preferred amount, the carbon black is 1% by mass or less, the azine dye is 1% by mass or less, and the inorganic pigment is 5% by mass or less.

[0157] By adding the above amount, the impact resistance and mechanical properties can be well balanced. In addition, in the case of applications requiring flame retardancy, the above amount is preferred from the perspective of flame retardancy.

[0158] (Inorganic filler)

[0159] In addition to the above-mentioned components, an inorganic filler may be added to the thermoplastic resin composition at any stage as necessary within a range that does not impair the effects of the present embodiment.

[0160] As the above-mentioned inorganic filler, fibrous, granular, plate-like or needle-like inorganic reinforcing materials such as glass fiber, potassium titanate fiber, gypsum fiber, brass fiber, ceramic fiber, boron whisker fiber, mica, talc, silicon oxide, calcium carbonate, kaolin, calcined kaolin, wollastonite, xonotlite, apatite, glass beads, glass flakes, titanium oxide can be enumerated. These inorganic fillers can be used in combination of more than 2 kinds. Among these, as a more preferred inorganic filler, glass fiber, carbon fiber, glass beads can be enumerated. In addition, inorganic fillers can also use materials that have been surface-treated using surface treatment agents such as silane coupling agents by known methods. Among them, natural ore-based fillers may usually contain trace amounts of iron elements, so it is necessary to select materials that are refined and have removed iron elements to use.

[0161] When the entire thermoplastic resin composition is taken as 100% by mass, the specific addition amount of each of the inorganic fillers is preferably 40% by mass or less, more preferably 35% by mass or less, and even more preferably 30% by mass or less.

[0162] The preferred amount of the inorganic filler added is preferably 50% by mass or less, more preferably 40% by mass or less, and even more preferably 35% by mass or less, based on 100% by mass of the entire thermoplastic resin composition.

[0163] The inorganic filler may be a surface-treated material, and a known material may be used. A fibrous filler or a plate-like filler is preferred.

[0164] Examples of the fibrous filler include, but are not limited to, glass fibers, carbon fibers, whiskers such as potassium titanate whiskers, and calcium silicate (wollastonite).

[0165] Examples of the plate-like filler include, but are not limited to, glass flakes, mica, and talc.

[0166] These may be used alone or in combination of two or more. Among the above fillers, glass fiber is most preferred from the viewpoint of rigidity and water resistance.

[0167] The surface treatment for the inorganic filler is not particularly limited, and for example, surface treatment using various coupling agents such as silane and titanate can be cited. In particular, from the perspective of improving the adhesion between the resin and the surface-treated inorganic filler, improving the vibration fatigue characteristics and impact resistance of the resin composition, surface treatment using silane coupling agents such as aminosilane and epoxysilane is preferred. In addition, if included in the surface treatment agent containing an acid functional group, it is preferred from the perspective of water resistance.

[0168] It should be noted that whether the judgment of including the above-mentioned acid functional group can be judged by whether the peak from the acid is detected when the surface treatment agent of the glass fiber is extracted into chloroform and measured by PyGCMS. Particularly from the aspect of water resistance, it is preferred to use a glass fiber that can detect the peak from the carboxylic acid.

[0169] As for the acid constituting the compound containing the acid functional group, as unsaturated carboxylic acid or its derivative, there can be mentioned unsaturated carboxylic acids such as maleic acid, fumaric acid, itaconic acid, acrylic acid, tetrahydrophthalic acid, citraconic acid, crotonic acid, isocrotonic acid, etc., and as its derivative, there can be mentioned, for example, acid anhydride, acid halide, amide, imide, ester, etc. Specifically, maleic anhydride, acetic anhydride, succinic anhydride, monomethyl maleate, dimethyl maleate, maleimide, glycidyl maleate, etc. can be illustrated.

[0170] The silane coupling agent (silane coupling agent) used in the above surface treatment is not particularly limited, but is preferably 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethoxysilane, 3-glycidoxypropyltrimethoxysilane, or 3-glycidoxypropyltriethoxysilane.

[0171] As a method for surface treatment of the above-mentioned inorganic filler, for example, when the inorganic filler is glass fiber, a method of applying a sizing agent and a silane coupling agent to the surface of the fibrous inorganic filler when spinning and bundling, and then drying can be cited. When the inorganic filler is in the form of short fibers or powder, a method of immersing these fillers in a silane coupling agent solution and then drying can be cited. Here, the temperature during drying is preferably 100° C. or above.

[0172] The glass fiber is obtained by melt spinning commonly supplied E glass (Electrical glass), C glass (Chemical glass), A glass (Alkali glass), S glass (High strength glass), D glass, R glass, and alkali-resistant glass. A preferred example of this embodiment is E glass, and D glass is also preferred in order to achieve a lower dielectric.

[0173] In order to further reduce the dielectric properties of the resin composition, the above-mentioned inorganic fiber is preferably a low-dielectric inorganic fiber, and more preferably a low-dielectric glass fiber. The low-dielectric inorganic fiber refers to an inorganic fiber with a low dielectric constant and a low dielectric loss tangent, and for example, an inorganic fiber with a dielectric constant of less than 7 can be exemplified. The dielectric constant here is a value measured according to ASTM D 150.

[0174] As such low dielectric glass fibers, for example, glass fibers containing 65 to 85% by mass of SiO2, 15 to 30% by mass of B2O3, 0 to 4% by mass of sodium oxide (Na2O) and / or potassium oxide (K2O), and 0 to 4% by mass of other components (the total amount here does not exceed 100% by mass, and preferably the total is 100% by mass). Glass fibers with a large amount of B2O3 are known to have a low dielectric constant.

[0175] The thermoplastic resin composition may further contain 0.1 to 300.0 parts by mass of talc relative to 100 parts by mass of the laser direct structuring additive. By including talc, dimensional stability and product appearance can be improved, and the growth rate of the plating layer can be increased. In addition, by including talc, even if the content of the LDS additive is reduced, the plating property of the resin molded product can be improved.

[0176] Talc surface-treated with at least one compound selected from polyorganohydrogensiloxanes and organopolysiloxanes can be used. In this case, the amount of siloxane compound attached to the talc is preferably 0.1 to 5% by mass of the talc.

[0177] The number average particle size of the talc is preferably 0.1 to 50 μm, more preferably 0.1 to 25 μm. Talc is generally flaky, and the length of the longest part is taken as the average particle size. Regarding the number average particle size of talc, from an image obtained by observation using an electron microscope, talc of the particle size measurement object is randomly extracted, and its particle size is measured, and the number average particle size is calculated based on the obtained measured value. The observation magnification is set to 1,000 times, and the number of measurements is set to be 1,000 or more for measurement.

[0178] In addition, in the above-mentioned thermoplastic resin composition, talc may contain only one kind or two or more kinds.

[0179] In the communication device components of this embodiment, it is preferred to use low dielectric constant materials in most cases, but in order to achieve miniaturization, it is necessary to control the dielectric constant, and sometimes a high dielectric constant material is required. In this case, the dielectric constant can be controlled by adding an inorganic filler with a high dielectric constant.

[0180] For example, titanium oxide, calcium carbonate, etc. are exemplified. Even when a high dielectric constant is required, it is preferable to keep the dielectric loss tangent low. Materials whose dielectric loss tangent increases due to water absorption, etc., deteriorate the performance as an antenna.

[0181] (Other ingredients)

[0182] It should be noted that, in addition to the above-mentioned components, the above-mentioned thermoplastic resin composition may also contain plasticizers (low molecular weight polyolefins, polyethylene glycol, fatty acid esters, etc.), antistatic agents, nucleating agents, flow improvers, reinforcing agents, various peroxides, spreading agents, copper-based heat stabilizers, organic heat stabilizers represented by hindered phenol-based antioxidants, antioxidants, ultraviolet absorbers, light stabilizers, lubricants such as ethylene bisstearamide, and modifying materials such as maleic anhydride as other additive components.

[0183] The specific preferred addition amount of each of the other components is 15% by mass or less, more preferably 13% by mass or less, and even more preferably 10% by mass or less, when the entire thermoplastic resin composition is taken as 100% by mass.

[0184] The preferred amount of other components added is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, based on 100% by mass of the entire thermoplastic resin composition.

[0185] (Method for producing thermoplastic resin composition)

[0186] The thermoplastic resin composition can be produced by melt-kneading the components constituting the matrix resin (A), the LDS additive (B), and, if necessary, a colorant, an inorganic filler, and other components.

[0187] As the melt kneading machine for melt kneading, for example, single screw extruder, multi-screw extruder including twin screw extruder, heating melt kneading machine based on roll, kneading machine, Brabender plastometer, Banbury mixer, etc. can be cited but not limited to, in particular, from the aspect of kneading property, twin screw extruder is preferred. Specifically, ZSK series manufactured by WERNER & PFLEIDERER, TEM series manufactured by TOSHIBA MACHINE CO., LTD., TEX series manufactured by Nippon Steel Works, Ltd., etc. can be cited.

[0188] The melt kneading temperature at this time can be selected as a temperature at which the crystalline resin can be heated and melted at a temperature higher than the melting point of the crystalline resin and can be smoothly processed, and can be selected as a temperature at which the amorphous resin can be heated and melted at a temperature higher than the glass transition temperature and can be smoothly processed, and can usually be arbitrarily selected from 200 to 370° C. It is particularly preferred to process at a processing temperature higher than 260° C., and by achieving a certain viscosity, the distance between particles can be controlled.

[0189] A preferred production method using an extruder is described below.

[0190] The L / D (barrel effective length / barrel inner diameter) of the extruder is preferably 20 or more and 60 or less, more preferably 30 or more and 50 or less.

[0191] There is no particular limitation on the structure of the extruder. For example, it is preferred to set the first raw material supply port on the upstream side relative to the flow direction of the raw material, set the first vacuum exhaust port downstream of the first raw material supply port, set the second raw material supply port downstream of the first vacuum exhaust port (the third and fourth raw material supply ports can be further set downstream of the second raw material supply port as required), and further set the second vacuum exhaust port downstream of the second raw material supply port. In the case of using a liquid adding pump, from the perspective of exhibiting flame retardancy, it is further preferred to have a liquid adding pump downstream of the second raw material supply port and a second vacuum exhaust port downstream of the liquid adding pump. In addition, there is no particular limitation on the raw material supply method for the second, third, and fourth raw material supply ports. It can be a method of simply adding from the upper open port of the raw material supply port, or a method of adding from the side open port using a forced side feeder. In particular, from the perspective of stable supply, it is preferred to use a forced side feeder to add from the side open port.

[0192] In particular, it is more preferable to provide a kneading section upstream of the first vacuum exhaust port, to provide a kneading section between the first vacuum exhaust port and the second raw material supply port, and to provide a kneading section between the second to fourth raw material supply ports and the second vacuum exhaust port.

[0193] In addition, the structure of the screw provided in the barrel is not particularly limited, and it can be a structure in which right-handed, left-handed, orthogonal (N-type), and reverse feed (L-type) kneading disk components are appropriately provided. In particular, the following structure is preferred because it can control the dispersion state of the (B) LDS additive within a specific range. In this structure, at least one orthogonal (N-type) kneading disk component and at least one reverse feed (L-type) kneading disk component are provided between the first raw material supply port and the second raw material supply port, and at least one orthogonal (N-type) kneading disk component is provided between the liquid adding pump and the vacuum exhaust port downstream of the liquid adding pump. It is particularly preferred to include more than one reverse screw so that the distance between particles can be controlled. However, if there are too many reverse screws, the mixing becomes too much, which is not preferred. The number of reverse screws is preferably more than 2 and less than 5. The reverse screw can be in any shape, such as reverse feed, reverse kneading, etc., and refers to a screw in the opposite direction to the feed direction.

[0194] When adding liquid raw materials, the liquid raw materials can be directly sent into the barrel system by using a liquid adding pump, etc. in the extruder barrel part for addition. There is no particular limitation as the liquid adding pump, for example, a gear pump, a flange pump, etc. can be cited, preferably a gear pump. At this time, from the aspect of reducing the load applied to the liquid adding pump and improving the operability of the raw material, it is preferred to use a heater, etc. to heat the part of the flow path of the liquid raw material that becomes the tank storing the liquid raw material, the piping between the tank and the liquid adding pump, the piping between the pump and the extruder barrel, etc., to reduce the viscosity of the liquid raw material.

[0195] The method of supplying raw materials to the above-mentioned 2nd to 4th raw material supply ports is not particularly limited. Compared with simply adding and supplying from the open ports of the 2nd to 4th raw material supply ports of the extruder, the method of supplying from the open port on the extruder side using a forced side feeder tends to be able to supply more stably, and is therefore preferred.

[0196] In particular, when the raw materials contain powders and it is desired to reduce the generation of crosslinked products or carbides due to the thermal history of the resin, it is more preferred to use a forced side feeder supplied from the side of the extruder, and it is further preferred to provide forced side feeders at the second to fourth raw material supply ports to supply these raw material powders separately. In particular, the (B) LDS additive is preferably provided at the second to fourth raw material supply ports to control the distance between particles.

[0197] When adding a liquid raw material, it is preferably added to an extruder using a plunger pump, a gear pump, or the like.

[0198] Furthermore, the upper openings of the second to fourth raw material supply ports of the extruder can also be used as openings for releasing air conveyed together.

[0199] There is no particular limitation on the melt-kneading temperature and screw speed in the melt-kneading step of the thermoplastic resin composition. For crystalline resins, a temperature can be selected at which the crystalline resin can be heated and melted above its melting point so that the processing can be smoothly performed. For amorphous resins, a temperature can be selected at which the amorphous resin can be heated and melted above its glass transition temperature so that the processing can be smoothly performed. Usually, any temperature can be selected from 200 to 370°C, and the screw speed can be set to 100 to 1200 rpm.

[0200] As one of the specific methods for preparing the above-mentioned thermoplastic resin composition using a twin-screw extruder, for example, the following method can be cited: each component constituting the component (A) and the raw material titanium dioxide are supplied to the first raw material supply port of the twin-screw extruder, the heating and melting zone is set to the melting temperature of the thermoplastic resin, and melt-kneading is performed at a screw speed of 100 to 1200 rpm, preferably 200 to 500 rpm. In addition, regarding the position where each component constituting the component (A) and the raw material titanium dioxide are supplied to the twin-screw extruder, they can be supplied all at once from the first raw material supply port of the extruder as described above, or a second raw material supply port, a third raw material supply port, and a fourth raw material supply port can be set to supply each component separately.

[0201] In addition, in the case of reducing the crosslinked products and carbide produced by the thermal history of the resin in the presence of oxygen, it is preferred that the oxygen concentration of each process pipeline in the addition path added by each raw material to the extruder is maintained at less than 1.0 volume %. As the above-mentioned addition path is not particularly limited, as a specific example, a weight feeder, a pipe, a feeding hopper, and a twin-screw extruder that are successively provided with a pipe from a storage tank and a fluid replenishing tank can be cited. As a method for maintaining the above-mentioned low oxygen concentration is not particularly limited, it is effective to introduce an inert gas into each process pipeline that improves airtightness. Usually, it is preferred to introduce nitrogen and maintain the oxygen concentration at less than 1.0 volume %.

[0202] Regarding the method for producing the above-mentioned resin composition, when the thermoplastic resin in the component (A) contains a powdered component (volume average particle size is less than 10 μm), when the above-mentioned resin composition is produced using a twin-screw extruder, it will bring about an effect of further reducing the residue at the screw of the twin-screw extruder, and further, in the resin composition obtained by the above-mentioned production method, it can bring about an effect of reducing the generation of black spot foreign matter, carbide, etc.

[0203] As a specific method for producing the thermoplastic resin composition, it is preferred to use an extruder in which the oxygen concentration at each raw material supply port is controlled to be less than 1.0% by volume and to carry out any one of the following methods 1 and 2.

[0204] 1. The manufacturing method is as follows: a part of the (A) component contained in the resin composition constituting the present embodiment is melt-kneaded (first kneading step), the total amount of the (B) LDS additive is supplied to the kneaded product in a molten state obtained in the first kneading step, and then melt-kneading is performed (second kneading step).

[0205] 2. The manufacturing method is as follows: a portion of the (A) component contained in the resin composition constituting the present embodiment is melt-kneaded (first kneading step), a portion of the (B) LDS additive is supplied to the molten kneaded material obtained in the first kneading step, and melt-kneading is performed (second kneading step), the remaining amount of the (B) LDS additive is supplied, and then melt-kneading is performed (third kneading step).

[0206] [Characteristics of the thermoplastic resin composition]

[0207] The properties of the molded article formed from the above-mentioned resin composition will be described below.

[0208] A higher Vickers softening temperature (° C.) of the thermoplastic resin composition constituting the communication device component of the present embodiment is preferred because the heat resistance is improved.

[0209] In addition, the said Vickers softening temperature is the value measured by the method described in the Example mentioned later.

[0210] The heat generation of high-frequency antenna components increases, and the higher the frequency, the greater the heat generation, so high heat resistance is required. In particular, high heat resistance is required in antenna components with a frequency of 1 GHz or more. From this perspective, a Vickers softening temperature of 90°C or more is required. The higher the Vickers softening temperature, the more preferred.

[0211] Moreover, as the deflection temperature under load (DTUL) (° C.) of the thermoplastic resin composition, a larger value indicates an improvement in heat resistance, which is preferred.

[0212] In addition, the deflection temperature under load (DTUL) is a value measured by the method described in the examples described later.

[0213] The heat generation of high-frequency antenna components increases, and the higher the frequency, the greater the heat generation, so a resin with high heat resistance is required.

[0214] In particular, in antenna components having a frequency of 1 GHz or higher, a molded body composed of a resin composition having a DTUL of 90° C. or higher is preferred, and the DTUL is more preferably 92° C. or higher, and particularly preferably 95° C. or higher. The higher the heat resistance, the more preferred.

[0215] In the communication device member of the present embodiment, the thermoplastic resin composition has a water absorption rate of 1.5% or less.

[0216] Generally speaking, antennas and other communication equipment components are often used in an open state, and if the water absorption is high, they will absorb moisture from the atmosphere. If water is absorbed, the dielectric constant will deteriorate as described below, and the antenna performance will be significantly reduced. From this perspective, the water absorption rate needs to be 1.5% or less, preferably 1.0% or less, and more preferably 0.5% or less. The water absorption rate is preferably a smaller value.

[0217] A smaller dielectric constant of the molded article constituting the communication device component of the present embodiment indicates an improvement in antenna performance, which is preferred.

[0218] In addition, the dielectric constant refers to a value measured by the method described in Examples below.

[0219] The dielectric loss tangent of the molded article composed of the above thermoplastic resin composition is preferably a smaller value, indicating a reduction in energy loss rate. In particular, the dielectric loss tangent is a parameter that has a risk of water absorption, and a thermoplastic resin composition that does not increase the dielectric loss tangent after immersion in hot water at 80°C for 144 hours, which is an indicator of the characteristics after long-term water absorption, is preferred. The less likely a material is to increase the dielectric loss tangent after immersion in water, the more likely it is to be a material that is not likely to absorb water even after long-term observation.

[0220] It should be noted that the dielectric loss tangent refers to a value measured by the method described in the examples described later.

[0221] In the communication device component of the present embodiment, the interparticle distance of the LDS additive in the thermoplastic resin composition is 2.2 to 3.2 μm. By being in such a dispersed state, the dielectric constant and dielectric loss tangent will not deteriorate under any molding conditions, so it is preferred. Although it is speculative, it is believed that by making the interparticle distance within this range, even if molding is performed at high temperature, a network of LDS additives that deteriorate dielectric properties will not be formed, and excellent antenna characteristics can be exhibited. From the same aspect, the interparticle distance of the above-mentioned LDS additive is preferably 2.3 to 3.0 μm, and more preferably 2.4 to 2.9 μm.

[0222] It should be noted that the distance between particles of the LDS additive is a value measured by the method described in Examples below.

[0223] It should be noted that the distance between particles of the LDS additive in the thermoplastic resin composition can be adjusted by adjusting the raw materials and controlling the kneading state in the extruder.

[0224] By controlling the initial particle size of the added LDS additive, the distance between particles can be controlled. It is also speculated that if the viscosity of the resin component is high, it is easy to mix, and if the viscosity is low, it is difficult to mix. However, compared with this, the effect of the injection position of the extruder and the dispersion adjustment by the screw structure described later is greater.

[0225] In addition, when the LDS additive is added to the extruder, the dispersion state can be controlled by adding it from the upstream, from the midstream, or from the downstream. When adding it from the midstream rather than the upstream or from the downstream rather than the midstream, the kneading time is shortened, and thus there is a tendency for the distance between particles to increase.

[0226] Furthermore, by appropriately setting the screw (particularly the kneading section) in the extruder, the kneading state can be controlled.

[0227] In the communication device member of the present embodiment, it is preferred that the maximum particle size of the LDS additive contained in the thermoplastic resin composition is 2.2 μm or more because the above inter-particle distance can be easily achieved.

[0228] It should be noted that the maximum particle size of the LDS additive is a value measured by the method described in the examples described later.

[0229] The interparticle distance can be easily achieved by adjusting the number of particles of the LDS additive contained in the field of view during observation. For example, when a field of view during observation under a microscope is set to 62.02 μm×39.77 μm, the number of particles is preferably 250 or less, and more preferably 220 or less.

[0230] It should be noted that the number of particles of the LDS additive is a value measured by the method described in the examples described later.

[0231] [Molded articles, parts for communication equipment]

[0232] The molded article constituting the communication device component of the present embodiment is composed of the above-mentioned thermoplastic resin composition. The above-mentioned molded article may be produced by any method without particular limitation, and may be produced by injection molding, for example.

[0233] Furthermore, the molded body produced by such a method may be used in a form in which a coating layer composed of a paint, a metal, another type of polymer, or the like is formed on the surface of the molded body.

[0234] The communication device component of the present embodiment has one or more of the above-mentioned molded bodies. The communication device component may have a structure in which a plurality of molded bodies are fitted together.

[0235] The communication device component of this embodiment has a conductive portion on the surface of the molded body. The conductive portion has conductivity and can be formed by coating a metal ink or plating.

[0236] The conductive portion may include one or more selected from the group consisting of a metal circuit, a metal wiring, and a metal base.

[0237] Furthermore, in the communication device component of the present embodiment, the conductive portion is formed by laser direct structuring.

[0238] It should be noted that the type of plating applied to the molded body is not particularly limited, and gold, silver, or copper can be used. Furthermore, plating containing a plurality of metals can also be used.

[0239] It should be noted that any metal can be used for metallic ink.

[0240] The communication device component of the present embodiment has high copper damage resistance and can reduce cracks after application and plating of the above-mentioned metal ink, which is also one of its characteristics.

[0241] The laser used is not particularly limited, and can be appropriately selected from known lasers such as YAG laser, excimer laser, and electromagnetic beam. The wavelength of the laser is not particularly limited.

[0242] If the above-mentioned molded body is irradiated with laser, only the part irradiated with laser is activated. In this activated state, the electroplating solution is brought into contact with the above-mentioned molded body. The above-mentioned electroplating solution is not particularly limited, and a known electroplating solution can be widely used. As the metal component, it is preferably an electroplating solution containing one or more of copper, nickel, silver, gold and palladium (especially an electroless electroplating solution), more preferably an electroplating solution containing one or more of copper, nickel, silver and gold (especially an electroless electroplating solution), and further preferably an electroplating solution containing copper (especially an electroless electroplating solution). That is, in the above-mentioned plating layer, the metal component preferably contains at least one of the above-mentioned metals.

[0243] In the method for forming a component for communication equipment of the present embodiment, a plating layer (circuit) having a width of less than 1 mm and further less than 150 μm (the lower limit is not particularly limited, for example, 30 μm or more) can be formed. In order to suppress corrosion and degradation of the formed plating layer (circuit), for example, nickel or gold can be used to further protect the above-mentioned plating layer after electroless plating. In addition, electrolytic plating can also be used after electroless plating to form the necessary film thickness in a short time.

[0244] When the surface of the molded body is coated with metal ink, there are various methods for bonding with resin. Even in the method requiring heat resistance such as the method of bonding using laser, the communication device component of this embodiment can be used.

[0245] For example, in the case of communication equipment components, the circuit pattern of the wiring board can be formed by drawing with a conductive metal paste using an inkjet method. The circuit pattern forming method can be a known method (see, for example, Japanese Patent Application Laid-Open No. 2002-324966).

[0246] The conductive metal paste used is a conductive metal paste in which metal superfine particles with a fine average particle size are uniformly dispersed in a thermosetting resin composition containing an organic solvent. The average particle size of the metal superfine particles with a fine average particle size is selected in the range of 1 to 100 nm. A material in which the surface of the metal superfine particles is coated with one or more compounds having groups containing nitrogen, oxygen, and sulfur atoms as groups that can coordinate and bond with the metal elements contained in the metal superfine particles can be appropriately used.

[0247] The metal ultrafine particles with a fine average particle size contained in the above-mentioned conductive metal paste can appropriately use particles composed of a metal selected from the group consisting of gold, silver, copper, platinum, palladium, tungsten, nickel, tantalum, bismuth, lead, indium, tin, zinc, titanium, and aluminum; or particles of an alloy composed of two or more metals.

[0248] The method for forming a circuit pattern comprises the following steps: a step of making the above-mentioned conductive metal paste into tiny droplets, spraying and coating them onto a substrate, and drawing a circuit pattern composed of a coating film of the above-mentioned conductive metal paste; and a step of heating the drawn coating film of the conductive metal paste at a temperature at least at which the above-mentioned thermosetting resin undergoes thermal curing.

[0249] As drawing means based on the inkjet method, there are thermal drawing means that generates bubbles by heating and bubbling to discharge droplets, and piezoelectric drawing means that discharges droplets by compressing a piezoelectric element.

[0250] The communication device component of this embodiment can be used in various applications such as electronic components such as sensors, connectors, switches, relays, conductive circuits, and antennas (particularly, portable electronic device components, communication base stations, and personal computer peripherals).

[0251] Example

[0252] The present embodiment will be described in further detail below using examples and comparative examples, but the present embodiment is not limited to these examples.

[0253] The raw materials used in Examples and Comparative Examples are as follows.

[0254] [raw materials]

[0255] (Aa) Polyphenylene ether

[0256] (Aa-1) Polyphenylene ether resin obtained by oxidative polymerization of 2,6-xylenol

[0257] The reduced viscosity (0.5 g / dL, chloroform solution, measured at 30° C.) of the polyphenylene ether resin (Aa-1) was 0.52 dL / g.

[0258] (Aa-2) Polyphenylene ether resin obtained by oxidative polymerization of 2,6-xylenol

[0259] The reduced viscosity (0.5 g / dL, chloroform solution, measured at 30° C.) of the polyphenylene ether resin (Aa-2) was 0.40 dL / g.

[0260] (Aa-3) Polyphenylene ether resin obtained by oxidative polymerization of 2,6-xylenol

[0261] The reduced viscosity (0.5 g / dL, chloroform solution, measured at 30° C.) of the polyphenylene ether resin (Aa-3) was 0.32 dL / g.

[0262] (B)LDS additives

[0263] (B-1) Antimony-doped tin oxide (trade name "StanoStat CP05" manufactured by Keeling & Walker Limited; average particle size 1.25 μm)

[0264] (B-2) Antimony-doped tin oxide (trade name "Iriotec 8815" manufactured by Merck; average particle size 0.45 μm)

[0265] (B-3) Copper chromate (trade name "LD14" manufactured by Shepherd Color; average particle size 0.65 μm)

[0266] (B-4) Copper chromate (trade name "SPP-3089" manufactured by Vibrantz Technology; average particle size 1.40 μm)

[0267] The particle size of each LDS additive was measured by curing the epoxy resin in which the LDS additive particles were dispersed, cutting the cross section with a Microtome.

[0268] The morphology of the sample was confirmed using SEM-EDX, using SU-8220 (Hitachi High-Technologies) and Quantax SYSTEM (Bruker) for EDX.

[0269] The measurement conditions were as follows: during image acquisition, the acceleration voltage was 1.5 kV and the imaging mode was composition (LA) imaging; during EDX measurement, the acceleration voltage was 10 kV and the analysis mode was mapping analysis.

[0270] The magnification was set to ×5,000 (SEM image capture), ×2,000, or ×5,000 (EDX mapping measurement).

[0271] This image was used to perform image analysis to measure the average particle size of the LDS additive.

[0272] Regarding the conditions for image analysis, the mapping images of Cr and Sn obtained by EDX mapping measurement (shooting magnification × 2,000 or × 5,000) were subjected to binarization processing using image processing software, and the particle size, interparticle distance, and particle number of the extracted particles were measured. For the 2000-fold image, the field of view of 62.02 × 39.77 (μm) was set as n = 1, and for the 5000-fold image, the field of view of 24.81 × 15.91 (μm) was set as n = 1, and for image analysis, n = 2 or more was performed. ImageJ1.52a was used as the software.

[0273] At 2000 times for areas < 0.03 μm 2 Particles <0.01μm at 5000 times 2 Particles that are larger than 0.03 mm in diameter cannot be distinguished from interference factors and are therefore excluded. In addition, particles that cross the boundary of the field of view are excluded. The equivalent circle diameter is calculated from the area of ​​each particle and the particle size is measured.

[0274] (Ab) a block copolymer comprising at least one block mainly composed of aromatic vinyl monomer units and at least one block mainly composed of conjugated diene monomer units and / or a hydrogenated product of the block copolymer

[0275] Hydrogenated block copolymer (trade name "Tuftec (registered trademark) H1051" manufactured by Asahi Kasei Corporation)

[0276] (Ac) Polystyrene resin

[0277] (Ac-1) Polystyrene (trade name "GPPS685" manufactured by PS Japan Co., Ltd.)

[0278] (Ac-2) High impact polystyrene (trade name "CT-60" manufactured by PETRO-CHEMICALS)

[0279] (Ad) Polyamide 6,6 (hereinafter referred to as PA66)

[0280] 2400g of an equimolar salt of adipic acid and hexamethylenediamine, 100g of adipic acid, and 2.5 liters of pure water were put into a 5-liter autoclave and stirred thoroughly. After the atmosphere in the autoclave was fully replaced with nitrogen, it took about 1 hour to heat up from room temperature to 220°C under stirring. At this time, the gauge pressure in the autoclave was 1.76MPa based on the natural pressure of water vapor. Then, the water was removed from the reaction system while continuing to heat in a manner that the pressure would not reach more than 1.76MPa. Further, after 2 hours, when the internal temperature reached 260°C, the internal pressure was reduced to 0.2MPa in about 40 minutes by opening and closing the autoclave valve while continuing to heat. It took about 8 hours to cool to room temperature thereafter. After cooling, the autoclave was opened, about 2kg of polymer was taken out, and crushed.

[0281] The obtained polyamide had Mw = 38700 and Mw / Mn = 2.1. Mw and Mn were determined using GPC (mobile layer: hexafluoroisopropanol, standard substance: PMMA (polymethyl methacrylate)).

[0282] The terminal amino group concentration was measured according to the method for measuring the terminal amino group concentration described in Examples of Japanese Patent Application Laid-Open No. 7-228689, and the terminal amino group concentration was 38 μmol / g.

[0283] (Ae) MFR = 2 g / 10 min polypropylene homopolymer

[0284] (Af) Polyethylene resin

[0285] (Af-1) High-density polyethylene resin ("Suntec-HD B161" manufactured by Asahi Kasei Corporation)

[0286] (Af-2) High-density polyethylene resin ("Suntec-HD J320" manufactured by Asahi Kasei Corporation)

[0287] (C~E) Other ingredients

[0288] (C) Ethylene bisstearamide: "KAO WAXEB-G" manufactured by Kao Corporation

[0289] (D) Maleic anhydride ("Crystal MAN" manufactured by NOF Corporation)

[0290] (E) Calcium carbonate (SL-2200 manufactured by Takehara Chemical Industry Co., Ltd.)

[0291] (MF) Inorganic filler

[0292] (MF-1) Glass fiber (ECS03-T249 manufactured by Nippon Electric Glass Co., Ltd.)

[0293] (MF-2) Glass flake (MEG160FY M06 made by Nippon Sheet Glass Co., Ltd.)

[0294] (MF-3) Talc (Crown Talc PK-MMB manufactured by Matsumura Industry)

[0295] (FR) Flame retardant

[0296] (FR-1) Made by Daihachi Chemical Co., Ltd. Trade name: E890

[0297] (FR-2) manufactured by Daihachi Chemical Co., Ltd., trade name PX-200

[0298] [Examples 1 to 14, Comparative Examples 1 to 12]

[0299] The composition shown in Table 1 and Table 2 is mixed, and a twin screw extruder ZSK-40 (manufactured by COPERION WERNER & PFLEIDERER, Germany) is used to manufacture the resin composition. In the twin screw extruder, the first raw material supply port is arranged on the upstream side relative to the flow direction of the raw material, the first vacuum exhaust port is arranged downstream thereof, the second raw material supply port is arranged downstream thereof, the third raw material supply port is arranged downstream thereof, and the second vacuum exhaust port is further arranged downstream thereof. In addition, as required, a liquid adding pump and a vacuum exhaust port are further provided downstream of the first raw material supply port, and their positions are suitably changed as required.

[0300] Here, four kneading sections were provided (one between the first supply port and the first vacuum exhaust port, one between the first vacuum exhaust port and the second supply port, one between the second supply port and the third supply port, and one between the third supply port and the second vacuum exhaust port). The number of reverse feed (L-shaped) kneading disk members described in the table was arranged in the four kneading sections.

[0301] Using the extruder set as described above, the components were added according to the composition and addition method shown in Tables 1 and 2, and melt-kneaded under the conditions of extrusion temperature of 250 to 320° C., screw speed of 300 rpm, and discharge rate of 100 kg / hour to produce pellets.

[0302] [Evaluation method]

[0303] The following evaluations were performed using the resin compositions obtained in Examples and Comparative Examples.

[0304] (1) Dielectric constant and dielectric loss tangent

[0305] The obtained resin composition pellets were supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) with the cylinder temperature set at 250-290°C, and a 60 mm × 60 mm × 0.9 mm flat plate was produced under the conditions of a mold temperature of 70-130°C, an injection pressure of 200 MPa, an injection time of 10 seconds, and a cooling time of 20 seconds. The dielectric constant and dielectric loss tangent at 2.5 GHz were measured under the following conditions.

[0306] Measurement frequency: 2.5GHz

[0307] Measurement equipment: 10MHz to 43.5GHz PNA network analyzer N5224B, 10GHz split dielectric resonator N1501AE10

[0308] Measurement environment conditions: room temperature 23°C, humidity 50%

[0309] (2) Dielectric loss tangent during high temperature molding

[0310] The obtained resin composition pellets were supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) with the cylinder temperature set at 340°C, and a 60 mm × 60 mm × 0.9 mm flat plate was produced under the conditions of a mold temperature of 70 to 130°C, an injection pressure of 200 MPa, an injection time of 10 seconds, and a cooling time of 20 seconds. The dielectric loss tangent at 2.5 GHz was measured under the same conditions as (1).

[0311] (3) Dielectric loss tangent when absorbing water

[0312] The obtained resin composition pellets were supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) with the cylinder temperature set at 340°C, and a 60 mm × 60 mm × 0.9 mm flat plate was produced under the conditions of a mold temperature of 70-130°C, an injection pressure of 200 MPa, an injection time of 20 seconds, and a cooling time of 20 seconds. After being immersed in hot water at 80°C for 144 hours, the dielectric loss tangent at 2.5 GHz was measured under the same conditions as (1).

[0313] (4) Heat resistance

[0314] (4-1) Vickers softening temperature

[0315] The obtained pellets of the resin composition were supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) whose cylinder temperature was set to 340°C, and a 60 mm × 60 mm × 0.9 mm flat plate was produced under the conditions of a mold temperature of 70 to 130°C, an injection pressure of 200 MPa, an injection time of 10 seconds, and a cooling time of 20 seconds. The flat plate was cut into any size, and the obtained test piece was used to test the test load: 50 N, the tip shape of the indenter: cylindrical cross-sectional area 1 mm 2 The measurement was carried out under the conditions of a temperature increase rate of 50°C / hr and a number of measurements n=2.

[0316] As an evaluation standard, a higher value of the Vickers softening temperature indicates better heat resistance and is more advantageous in material design for the purpose.

[0317] (4-2) Deflection temperature under load (DTUL)

[0318] The pellets of the obtained resin composition were supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) with a barrel temperature set at 250-350°C, and an ISO dumbbell-shaped specimen for evaluation was prepared under the conditions of a mold temperature of 70-130°C, an injection pressure of 200 MPa, an injection time of 20 seconds, and a cooling time of 15 seconds. The ISO dumbbell-shaped specimen was cut to prepare a specimen for measuring the load deformation temperature (DTUL). Using the above-mentioned specimen for measuring the load deformation temperature, the load deformation temperature: DTUL (ISO 75: 1.80 MPa load) was measured.

[0319] The larger the value, the better the heat resistance is judged to be.

[0320] (5) Morphology

[0321] (5-1) Maximum particle size

[0322] (5-2) Distance between particles

[0323] (5-3)Number of particles

[0324] For the ISO dumbbell-shaped sample formed under the same conditions as in (4) above, the periphery was cut off so that the central part corresponded to the observation target position and direction (MD direction), and then the cryosectioned cross section of the observation surface was prepared by trimming and cryosectioning. The RuO4-stained sample was then fixed on the SEM sample stage and subjected to conductive treatment to be used as a microscopic examination sample.

[0325] The morphology of the microscopic specimens was confirmed using SEM-EDX, using SU-8220 (Hitachi High-Technologies) and Quantax SYSTEM (Bruker).

[0326] The measurement conditions were as follows: during image acquisition, the acceleration voltage was 1.5 kV and the imaging mode was composition (LA) imaging; during EDX measurement, the acceleration voltage was 10 kV and the analysis mode was mapping analysis.

[0327] The magnification was set to ×5,000 (SEM image capture), ×2,000, or ×5,000 (EDX mapping measurement).

[0328] Image analysis was performed using this image to measure (5-2) the distance between particles of the LDS additive, (5-1) the maximum particle size, and (5-3) the number of particles.

[0329] Regarding the conditions for image analysis, based on the mapping images of Cr and Sn obtained by EDX mapping measurement (shooting magnification × 2,000), image processing software was used to perform binarization processing, and the particle size, inter-particle distance, and particle number of the extracted particles were measured. Regarding the number of particles, when the particles are fine and more than 1,000 particles are observed in one image, the magnification is increased and observation is performed at × 5,000. Regarding the number of particles at this time, in order to match × 2,000, it is made 6.25 times. For the 2,000-fold image, the field of view of 62.02 × 39.77 (μm) is n = 1, and for the 5,000-fold image, the field of view of 24.81 × 15.91 (μm) is n = 1, and for image analysis, n = 2 or more. ImageJ 1.52a was used as the software. At this time, for areas less than 0.03 μm in the case of 2,000 times, 2 Particles smaller than 0.01 μm are detected at 5000 times the 2 Particles that cannot be distinguished from interference factors are excluded. Particles that cross the boundary of the field of view are excluded. Regarding the particle size, it is the value obtained by converting the equivalent circle diameter based on the area of ​​each particle. The average inter-particle distance is calculated based on {(the sum of each distance interval × degree)} / total degree. Regarding the inter-particle distance, the shortest distance is calculated based on the center of gravity of each particle.

[0330] (6) Antenna performance during high temperature molding

[0331] The simulation of antenna efficiency was performed under the following conditions.

[0332] Antenna substrate: 60×7×1mm 3 , whole surface solid GND, pattern width 1mm, thickness 25μm

[0333] ·Copper + Ni plating

[0334] ·Main substrate: 60×130×1mm 3 , dielectric constant 4.0, dielectric loss 0.020

[0335] Thickness 35μm Conductivity 5.8×10 7 S / m

[0336] Simulation device: MW STUDIO of CST

[0337] The reflection coefficient is adjusted to be below 6 dB in the working frequency band.

[0338] The antenna element length and matching circuit values ​​are adjusted to achieve the best match at 3.5 GHz, and the antenna efficiency at this time is calculated. Figure 3 as shown in (a) and (b). Figure 3 (a) shows the overall antenna structure. Figure 3 (b) shows an enlarged view of the antenna element portion.

[0339] Regarding the dielectric properties of the material (dielectric constant and dielectric loss tangent), the pellets of the obtained resin composition were supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) with the barrel temperature set at 340°C, and a 60 mm × 60 mm × 0.9 mm flat plate was produced under the conditions of a mold temperature of 70 to 130°C, an injection pressure of 200 MPa, an injection time of 20 seconds, and a cooling time of 20 seconds. The dielectric loss tangent at 5 GHz was measured under the following conditions.

[0340] ·Measurement frequency: 5GHz

[0341] ·Measurement equipment: 10MHz to 43.5GHz PNA network analyzer N5224B, 5.2GHz split dielectric resonator N1501AE10

[0342] ·Measurement environment conditions: room temperature 23℃, humidity 50%

[0343] The closer the value is to 0, the better the material is as an antenna. This simulation does not take plating properties into consideration, and therefore the simulation was performed on the assumption that even a material that is difficult to plate can function as an antenna.

[0344] (7) LDS plating properties

[0345] The pellets of the obtained resin composition are supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) whose barrel temperature is set to 280-320°C, and a 60mm×60mm×2.0mm flat plate is produced under the conditions of a mold temperature of 80°C, an injection pressure of 100MPa, an injection time of 15 seconds, and a cooling time of 20 seconds. The flat plate is activated using a laser irradiator (product name "Micro Line 3D16 0", manufactured by LPKF), and then the coating is imparted under the coating conditions of 57°C / 45 minutes using an electroless copper plating tank (product name "MID copper 100B1", manufactured by McDermid). Regarding the plating performance, the thickness of the plated copper is visually observed and evaluated and determined according to the following benchmarks. In addition, a cutter is used to cut out a cut groove of an ×-shaped mark for the completed coating, and the adhesion of the coating after the cellophane tape is pasted and peeled off is measured. Regarding the measurement results, the case where the plating layer was attached to the cellophane tape and peeled off was evaluated as poor adhesion.

[0346] ○ (good): good coating adhesion and coating adhesion

[0347] × (bad): The plating layer is not attached at all, or only a part of the plating layer is attached, and the plating adhesion is poor

[0348] (8) Water absorption

[0349] The pellets of the obtained resin composition were supplied to a small injection molding machine (trade name: EC75-SXII, manufactured by TOSHIBA MACHINE) whose barrel temperature was set to 280-320°C, and a 60mm×60mm×2.0mm flat plate was produced under the conditions of a mold temperature of 80°C, an injection pressure of 100MPa, an injection time of 15 seconds, and a cooling time of 20 seconds. The molded test piece was immersed in pure water for 24 hours at 23°C within 3 hours, and the weight change after immersion was evaluated as water absorption (%). The material with less water absorption can be said to be excellent.

[0350]

[0351]

[0352] Industrial Applicability

[0353] The thermoplastic resin composition and molded article of the present invention can be used as electronic components such as sensors, connectors, switches, relays, conductive circuits, antennas, etc. (especially portable electronic device components, communication base stations, personal computer peripherals) and other communication equipment components for various purposes. In particular, in the case of small components, high antenna characteristics can be exhibited regardless of molding conditions, and they can be used appropriately.

Claims

1. A thermoplastic resin composition, characterized in that The thermoplastic resin composition comprises a polyphenylene ether resin and a laser direct structuring additive, namely, an LDS additive. The distance between particles of the LDS additive is 2.2 μm to 3.2 μm, The thermoplastic resin composition has a Vickers softening temperature of 90° C. or higher and a water absorption rate of 1.5% or less.

2. A molded body, which is composed of a thermoplastic resin composition and has a conductive portion formed on the surface, characterized in that: The thermoplastic resin composition comprises a polyphenylene ether resin and a laser direct structuring additive, namely, an LDS additive. The distance between particles of the LDS additive in the thermoplastic resin composition is 2.2 μm to 3.2 μm, The thermoplastic resin composition has a Vickers softening temperature of 90° C. or higher and a water absorption rate of 1.5% or lower.

3. The molded article according to claim 2, wherein The conductive portion is formed by laser direct forming.

4. A communication device component, comprising the molded article according to claim 2 or 3.

5. The communication device component according to claim 4, wherein: The LDS additive is a compound comprising antimony and tin.

6. The component for communication equipment according to claim 4, wherein: When the thermoplastic resin composition was observed under a microscope, 220 or less LDS additives were observed in one field of view of 62.02 μm×39.77 μm.

7. The component for communication equipment according to claim 4, characterized in that: The maximum particle size of the LDS additive is greater than 2.2 μm.

8. The component for communication equipment according to claim 4, characterized in that: The content of the copper chromate compound as the LDS additive is less than 5 parts by mass based on 100 parts by mass of the thermoplastic resin composition.

9. The component for communication equipment according to claim 4, wherein: The content of the LDS additive is 3 parts by mass or more and less than 20 parts by mass based on 100 parts by mass of the thermoplastic resin composition.

10. The communication device component according to claim 4, wherein: The thermoplastic resin composition comprises a block copolymer and / or a hydrogenated product of the block copolymer, wherein the block copolymer comprises at least one block mainly composed of an aromatic vinyl monomer unit and at least one block mainly composed of a conjugated diene monomer unit.

11. The communication device component according to claim 4, wherein: The thermoplastic resin composition has a deflection temperature under load (DTUL) of 90° C. or higher.

12. The communication device component according to claim 4, wherein: The thermoplastic resin composition has a dielectric constant of 3.0 or less and a dielectric loss tangent of 0.008 or less.

13. The communication device component according to claim 4, wherein: The dielectric loss tangent of the thermoplastic resin composition after being immersed in hot water at 80° C. for 144 hours is 0.03 or less.

14. The communication device component according to claim 4, wherein: This is a component for an antenna.

Citation Information

Patent Citations

  • JP1975051197A

  • JP1977017880B2

  • Polyamide resin

    JP1995228689A

  • Flame-retardant, flame-retardant resin composition and flame-retardant resin molded product

    JP1999181429A

  • Patterned conductor structures, in particular fine patterned conductor structures, arranged on a non-conductive carrier material and method for producing the same

    JP2000503817A